“Vou continuar estudando, quero fazer o curso de Medicina”: processos de escolarização no quilombo da liberdade em São Luís-MA - COSTA, Karine Cristine (2023)
In view of the lack of studies in Brazil on schooling processes for black students and the choice of school establishment in quilombola communities, the purpose of this research was to analyze the relationship between the social practices of families, taking into account the social and symbolic space of the Urban Quilombo, dimensions of the student's life, including giving visibility to the agents' experiences and practices, their racial identity and the Afro-affective support network of which they are part. To achieve the proposed objective, the methodology had a qualitative approach, ethnographic description of the social and symbolic space, using as data collection instruments, direct observation followed by interviews with families and students. First, interviews were conducted with students from a public state school, considered the first to offer quilombola education, in the municipality of São Luís do Maranhão. In the second stage of the research, 06 black families from popular classes were interviewed with the intention of analyzing the social practices of the families that make up the urban quilombo with the school practices of their children. The results of the research revealed that the social and racial reality of the interviewed students leaves them at a disadvantage in relation to the white student, as they have to fight to continue studying and live with socio-racial inequalities, and to be tracing life prospects for themselves, because every are currently being highlighted. The social characteristics of the territory influence the families' educational strategies, especially in choosing (and not choosing) the educational establishment.